2017
DOI: 10.1371/journal.pone.0175440
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of advertising availability of prenatal ultrasound on uptake of antenatal care in rural Uganda: A cluster randomized trial

Abstract: In rural Uganda pregnant women often lack access to health services, do not attend antenatal care, and tend to utilize traditional healers/birth attendants. We hypothesized that receiving a message advertising that “you will be able to see your baby by ultrasound” would motivate rural Ugandan women who otherwise might use a traditional birth attendant to attend antenatal care, and that those women would subsequently be more satisfied with care. A cluster randomized trial was conducted across eight rural sub-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 22 publications
3
44
0
Order By: Relevance
“…Majority of the results were observational studies, with 7 prospective cohort studies, 3 cross‐sectional studies and 1 retrospective data analysis . Other study designs included a non‐blinded clustered randomised control trial, a pre‐post survey, a randomised control trial, a blinded investigational study, a field action report and a survey followed by a pilot project …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Majority of the results were observational studies, with 7 prospective cohort studies, 3 cross‐sectional studies and 1 retrospective data analysis . Other study designs included a non‐blinded clustered randomised control trial, a pre‐post survey, a randomised control trial, a blinded investigational study, a field action report and a survey followed by a pilot project …”
Section: Resultsmentioning
confidence: 99%
“…Africa was the region with the largest volume of literature, with 11 studies identified . Common themes explored included the utilisation of ANC, clinical knowledge and skills and patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…114 Management of unintended pregnancy The better availability and implementation of the management of unintended pregnancy. Examples of a proxy indicator is medications for induced abortion (mifepristone and misoprostol).…”
Section: Availability Of Ultrasoundmentioning
confidence: 99%